Zakat Produktif dan Kesejahteraan Mustahik dalam Perspektif Maqashid Syariah di BAZNAS Sragen - Marjany, Nawa; Kamil, Mustofa; Erialdy, Erialdy; Thoriqul Islam, Muhammad (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
One of the main challenges in zakat management is the low public understanding of the concept of productive zakat management. BAZNAS and LAZ, as official institutions, are often perceived as limiting community participation, which is exacerbated by concerns about bureaucracy and the potential for misappropriation of funds. This resistance is primarily caused by technical implementation constraints rather than the substance of zakat itself. Therefore, an alternative approach based on economic empowerment and the principles of maqashid sharia is needed. This study examines productive zakat management at BAZNAS Sragen using a qualitative case study approach. Data were collected through interviews, observation, and documentation, and then analyzed descriptively and qualitatively, concerning the maqashid sharia of Imam Al-Syatibi. The results show that BAZNAS Sragen's zakat management applies the principles of transparency, accountability, and empowerment of the mustahik through a structured fundraising mechanism, a verified distribution system, and Sharia-based planning and supervision.